PENERAPAN BENFORD'S LAW UNTUK MENDETEKSI DUGAAN KETIDAKPATUHAN MATERIAL PADA SPT TAHUNAN PPH ORANG PRIBADI - Adetya Candra Yuwana Putra; Maryadi (Scientax, 2021)
This study aims to examine whether the Individual Income Tax Return data set conforms to the Benford's Law pattern and to examine whether there are indications of material noncompliance in that data set based on the application of Benford's Law. This research is a quantitative research. The data source in this study is the taxation database owned by the Directorate General of Taxes (DGT), Ministry of Finance. The results of this study indicate that most of the Individual Income Tax Return data set variables conform to Benford's Law pattern and there are indications of material noncompliance in that data set. Tax officer, in this case account representatives and tax auditors are expected to be able to use the results of this study to carry out further analysis of the numerical class in the Individual Income Tax Return data set that is not appropriate and deviates from Benford's Law pattern. DGT, as a tax institution, is expected to consider the use of Benford's Law to assist the taxpayer supervision and inspection process.